COLLABORATIVE GOVERNANCE AS A SOLUTION TO THE INTEGRATION OF LEMBURSITU MARKET AND TERMINAL SUKABUMI CITY - Indri Silfia Rani; Dian Purwanti; Tuah Nur (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This research is motivated by the problem of the suboptimal operation of the Lembursitu Market in Sukabumi City which has been revitalized through the construction of the Jabar Juara People's Market which was inaugurated in August 2022 and has met the Indonesian National Standard (SNI 8152:2021). However, its implementation has not had a significant positive impact. The current market conditions are quiet and have not operated optimally, resulting in the revocation of the SNI label for the Lembursitu Market in Sukabumi City in 2023. Field findings show that many kiosks are unoccupied, market activity is minimal and the number of visitors is still low. Meanwhile, the condition of the terminal is also less supportive because the infrastructure is chaotic and unorganized. This condition indicates an imbalance in governance and a lack of synergy between the two public facilities. This study aims to examine the opportunities for integration of the Lembursitu Market and Terminal through a collaborative governance approach. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that meeting physical standards alone is not enough without being supported by effective market and terminal management. To optimize the integrated function of the market and terminal, collaborative cooperation between various parties is needed. By applying the principles of collaborative governance Ansell & Gash (2008), more effective integration can be achieved through open dialogue, increased trust between actors, and institutional design that supports sustainability between the market and the terminal. This study also highlights the importance of involving informal stakeholders such as traders, public transportation drivers who have proven to be important in forming a practical and sustainable integration model.